Heterogeneous Roles in Homogeneous âRepeated Words - عباسعلی وفایی (مطالعات زبانی و بلاغی)
Language plays different roles and it serves various âpurposes according to the speaker's intention and techniques. âThe written language of papers is different comparing to âother technical-scientific works. In addition, poetical âlanguage is not certainly the same as the elements used in the âwritings of direct speech. More important, there are a lot of âdifferences in the language used by authors or poets in a âsingle subject. These differences are revealed in the choice of âwords, synthesis, or substitution of the words i.e. the âsyntactic or paradigmatic relationship of the words. Mowlana âis considered to be a poet whose poetic language special âfeatures. One of those features is using repeated words in all âlinguistic categories which can be examined syntactically. An âissue that has been overlooked in the grammar of languages âand its homogeneous roles were neglected. This study is an âattempt to examine Mowlana's artistic techniques developing âthe repetition of words and to investigate its application in âheterogeneous roles of the words. These are the âdistinguishing features of Mowlana's poetic language. â